(3aJi GdCOZGds - (3cjHdjfL, QhOjGQOs; (3ShGM, SGde YHO GdeYRs; (3TGgjf, djfGs; (3eMeO, eMehO WGQbs ((3GdefhajI, eUQs (3MhGOjJ ddfTQ hGdJhRjYs, 2024)
(3JSQO bUU bUjQI eJYOOI CHQRgG bUI MjGI (B"(3eGhcdj(B" (3GdaJi GdPj jYjT aj GdCOZGd hGdPj JHfGg bWjY GdPFGH GdVGQjI hbO LQi JMhjd Jdc GdbUI EdCi CadGe heSdSdGJ YOjOI CHQRgG GdeSdSd GdcQJhfj GdTgjQ (B"(3eGhcdj aJi GdCOZGd(B" (3GdPj MXj HGfJTGQ hGSY Hjf eNJda GdaFGJ GdYeQjI, aQhGjI aJi GdCOZGd QhGjI cd ReGf hecGf hCjfeG GSJbQJ aj jO bGQF SjXd JCKjQgG aj bdHg WjdI MjGJgs
Keywords: (3GdCOH GdYQHjs; (3GdbUU GdYQHjI GdbUjQIs -- (3eUQs